Generalized Taylor and generalized Calvo price and wage-setting: Micro evidence with macro implications - Huw David Dixon; Hervé Le Bihan (Center for Economic Studies and ifo Institute (CESifo), 2010)
The Generalized Calvo and the Generalized Taylor model of price and wage-setting are, unlike the standard Calvo and Taylor counter-parts, exactly consistent with the distribution of durations observed in the data. Using price and wage micro-data from a major euro-area economy (France), we develop calibrated versions of these models. We assess the consequences for monetary policy transmission by embedding these calibrated models in a standard DSGE model. The Generalized Taylor model is found to help rationalizing the hump-shaped response of inflation, without resorting to the counterfactual assumption of systematic wage and price indexation.
Keywords: E31; E32; E52; J30; 330; contract length; steady state; hazard rate; Calvo; Taylor; wage-setting; price-setting; Lohnbildung; Betriebliche Preispolitik; Dynamisches Gleichgewicht; Modell-Spezifikation; Geldpolitik; Transmissionsmechanismus; Inflation; Theorie; Frankreich